The Impact of Self-Reported Hearing Difficulties on Memory Collaboration in Older Adults - Barnier, Amanda J.; Harris, Celia B.; Morris, Thomas; Strutt, Paul; Savage, Greg (Frontiers in Neuroscience, 2019)
Cognitive scientists and philosophers recently have highlighted the value of thinking about people at risk of or living with dementia as intertwined parts of broader cognitive systems that involve their spouse, family, friends or carers. By this view, we rely on people and things around us to “scaffold” mental processes such as memory. In this study we identified 39 long-married, older adult couples who are part of the Australian Imaging Biomarkers and Lifestyle (AIBL) Study of Ageing; all were healthy but half were subjective memory complainers. During two visits to their homes one week apart, we assessed husbands’ and wives’ cognitive performance across a range of everyday memory tasks working alone (Week 1) versus together (Week 2), including a Friends Task where they provided first and last names of their friends and acquaintances. As reported elsewhere, elderly couples recalled many more friends’ names working together compared to alone. Couples who remembered successfully together used well developed, rich, sensitive, and dynamic communication strategies to boost each other’s recall. But, if one or both spouses self-reported mild-to-moderate or significant hearing difficulties (56% of husbands, 31% of wives), they received less benefit from collaboration. Our findings imply that hearing loss may disrupt collaborative support structures that couples (and other intimate communicative partners) hone over decades together. We discuss the possibility that, cut off from the social world that scaffolds them, hearing loss may place older adults at greater risk of cognitive decline and dementia.